Peran Sikap Konsumsi Pakaian Yang Berkelanjutan Terhadap Niat Beli Thrift Fashion - laksana, yudhistira surya; Kuswati, Rini (Program Pascasarjana STIE Amkop Makassar, 2024)
The objective of this study is to examine how attitudes towards sustainable clothing consumption influence individuals' intentions to purchase thrift fashion items. The study employs a quantitative research approach, utilizing probability sampling through an accidental sampling method. Primary data collection is conducted via a structured questionnaire administered through Google Forms, employing a Likert scale to gauge respondents' fashion orientation, sustainable attitudes, conspicuous consumption habits, environmental consciousness, and purchase intentions. The study focuses on a population of 157 consumers interested in thrift fashion shopping in the region of Central Java. To analyze the data, PLS-SEM is employed, chosen for its flexibility in handling complex models with minimal data requirements. The data analysis utilizes the Partial Least Square (PLS) method, facilitated by SMARTPLS Software. The findings suggest that sustainable attitudes serve as a mediator in the relationship between fashion orientation, conspicuous consumption, environmental consciousness, and the intention to purchase fashion products.